2015
DOI: 10.1080/09168451.2014.991687
|View full text |Cite
|
Sign up to set email alerts
|

Lignans from the stems and leaves of Brandisia hancei and their effects on VEGF-induced vascular permeability and migration of HRECs and DLAV formation in zebrafish

Abstract: In our continuing search for novel antiangiogenic agents, a new lignan glycoside, (7R,8R)-1-(4-O-β-d-glucopyranosyl-3-methoxyphenyl)-2-{2-methoxy-4-[1-(E)-propene-3-ol]-phenoxyl}-propane-1,3-diol (1), along with three known lignans (2–4), were isolated from the 80% EtOH extract of Brandisia hancei stems and leaves. These isolates (1–4) were subjected to an in vitro bioassay to evaluate their effects on vascular endothelial growth factor (VEGF)-induced vascular permeability and migration of human retinal endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…The circular dichroism (CD) spectrum ( Figure S4) was measured to determine the configurations at C-7 and C-8 of compound 1. The results revealed that the CD spectrum of 1 showed positive signs in the region of 240-400 nm, indicating the 8S-configuration compared with those of reported analogs [15][16][17]. Furthermore, we confirmed the threo-configuration between H-7 and H-8 by confirming the large coupling constant (J 7,8 = 7.3 Hz) according to previous studies [18,19].…”
Section: Structure Determination Of Mtmnsupporting
confidence: 87%
“…The circular dichroism (CD) spectrum ( Figure S4) was measured to determine the configurations at C-7 and C-8 of compound 1. The results revealed that the CD spectrum of 1 showed positive signs in the region of 240-400 nm, indicating the 8S-configuration compared with those of reported analogs [15][16][17]. Furthermore, we confirmed the threo-configuration between H-7 and H-8 by confirming the large coupling constant (J 7,8 = 7.3 Hz) according to previous studies [18,19].…”
Section: Structure Determination Of Mtmnsupporting
confidence: 87%
“…In addition, two sugar units in substructure C (Figure 2 and (+)-pinoresinol di-O-β-ᴅ-glucopyranoside ( 14) [22], liriodendrin (15) [23], syringin (16) [24], and citrusin A (17) [25] (Figure 1) by comparison to literature data. In addition, compounds 2, 3, 8, and 11 were isolated for the first time from the genus Wikstroemia.…”
Section: Resultsmentioning
confidence: 88%
“…Sixteen known compounds were isolated and their structures were determined as 7-(β-ᴅ-glucopyranosyloxy)-7'-hydroxy-3-[(2-oxo-2 H -1-benzopyran-7-yl)oxy]-[8,8'-bis(2 H -1-benzopyran)]-2,2'-dione ( 2 ) [ 11 ], 6-(β-ᴅ-glucopyranosyloxy)-7-[(2-oxo-2 H -1-benzopyran-7-yl)oxy]-2 H -1-benzopyran-2-one ( 3 ) [ 9 ], rutarensin ( 4 ) [ 12 ], hirsutrin ( 5 ) [ 13 ], genkwanin 5-O-β-ᴅ-primeveroside ( 6 ) [ 14 ], (7 S ,8 R )-5-methoxydehydrodiconiferyl alcohol 4-O-β-ᴅ-glucopyranoside ( 7 ) [ 15 ], 9'-methoxydehydrodiconiferyl alcohol 4-O-β-ᴅ-glucopyranoside ( 8 ) [ 16 ], dehydrodiconiferyl alcohol-4-O-β-ᴅ-glucopyranoside ( 9 ) [ 17 ], (+)-pinoresinol ( 10 ) [ 18 ], 4,4'-dimethoxy-3'-hydroxy-7,9':7',9-diepoxylignan-3-O-β-ᴅ-glucopyranoside ( 11 ) [ 19 ], (+)-medioresinol 4-O-β-ᴅ-glucopyranoside ( 12 ) [ 20 ], (+)-springaresinol-4''-O-β-ᴅ-monoglucopyranoside ( 13 ) [ 21 ], (+)-pinoresinol di-O-β-ᴅ-glucopyranoside ( 14 ) [ 22 ], liriodendrin ( 15 ) [ 23 ], syringin ( 16 ) [ 24 ], and citrusin A ( 17 ) [ 25 ] ( Figure 1 ) by comparison to literature data. In addition, compounds 2 , 3 , 8 , and 11 were isolated for the first time from the genus Wikstroemia .…”
Section: Resultsmentioning
confidence: 99%
“…The activity of Hif-1α is induced by the decrease in the bioavailability of oxygen for the cells -being classi ed as a state of hypoxia -triggering important metabolic alterations, still little elucidated in DM [18][19][20][21] . In this state there are also changes in the expression of VEGF, a highly speci c dimeric glycoprotein that promotes migration and inhibits the process of cell apoptosis [22][23][24] . Due to the scarcity of studies on effective markers capable of identifying the onset of metabolic alterations in DM, this study aimed to evaluate the expression pro le of the Mct1, Mct4, Cd147, Hif-1α and Vegf genes in diabetic rats, in target tissues such as heart, brain and kidney, and in blood samples, in different periods after the onset of the disease (7, 21, 30 and 40 days), aiming to evaluate the subchronicity of this disease.…”
Section: Introductionmentioning
confidence: 99%